An Inexpensive Suturing Training Model - Kumaresan, Ramesh (J Maxillofac Oral Surg, 2013)
INTRODUCTION: Demonstrations and training on live-subjects are not always the optimal means of introducing the students to minor oral surgery. Hence, the use of teaching models permit the students to handle the surgical instruments in a limited field under a semi-realistic circumstance and also helps in developing psychomotor skills in an non stressed situation. One among the competent exercise in oral surgery is suturing. Though there exist a variety of commercially available suturing training models, cost factor restrain their acquirement in few units. METHODS & MATERIALS: This paper describes the construction of a simple and cost-effective suturing model for preclinical training. The construction of this model requires an orange peel, putty impression material and plaster of paris. This suturing model can be created in ten minutes. CONCLUSION: This model can be constructed by the students with minimal effort and low cost in order to practice suturing.